Impact of teachers’ psychological well-being on usability of systematic guidance for constructing achievement test items - Zyaliah @ Maya Ramdan; Christina Andin; Aslina Baharum (Malaysian Journal of Social Sciences and Humanities (MJSSH), 2024)
Assessment in education is crucial for revealing student achievement potential and motivating learners. Teachermade tests, a common assessment tool, must be welldesigned and aligned with learning objectives to measure student performance effectively. The Systematic Guidance System (SiPantik) was developed to assist teachers in constructing quality test items. This study evaluates SiPantik's usability and its impact on teachers' psychological well-being. Using the USE Questionnaire, the study investigates how the system's ease of use, usefulness, and satisfaction reduce stress and enhance teachers' sense of competence and control. The findings indicate that SiPantik is perceived as a supportive and efficient tool that positively influences psychological well-being by reducing administrative burdens and making the teaching process more enjoyable. The study underscores the importance of user-centric design in educational tools, as the usability and satisfaction provided by SiPantik are closely linked to improved job satisfaction, mental health, and overall life satisfaction. The positive impact of SiPantik highlights the broader benefits of well-designed systems in fostering a supportive and productive educational environment.